A conversation with an imagined Israeli filmmaker named Avi Mograbi. - Zaatari, Akram (Aubervilliers : Les Laboratoires d'Aubervilliers, 2012)
"In April 2010, during his residency at Les Laboratoires d'Aubervilliers, Akram Zaatari attempted to write, improvise, and deliver a conversation with an imagined Israeli filmmaker, giving him the name Avi Mograbi ... this text sheds light on the conflict between Israel and Lebanon, and the complexity of its recent history, of drafting borders, mobility of individuals, and the concept of 'the enemy,' while simultaneously questioning what it means to be a documentary filmmaker today"--
boek
Keywords: Zaatari, Akram; Mograbi, Avi